Long bone fractures in impala (Aepyceros melampus) : a classification system and review of 55 cases - Hartman, Marthinus Jacobus (University of Pretoria, 2025)
Mini Dissertation (MMedvet (Small Animal Surgery))--University of Pretoria, 2019.